Determinación del antígeno Helicobacter pylori por el método de inmunocromatografía en los estudiantes del Instituto Tecnológico 12 de Febrero de Zamora y su relación con los factores de riesgo. - Guaya Iñiguez, Diana Eugenia (2015)
Helicobacter pylori is a gram-negative bacterium that colonizes the gastric epithelium and is the Etiological Agent of gastrointestinal diseases such as gastritis, duodenal ulcer, gastric ulcer and it is an important risk factor for the development of gastric cancer. The purpose of this study was to determine the antigen H. pylori in high school students attending the “Fefruary 12 Institute of Technology” in Zamora, through the analysis of stool samples using the immunochromatography method and its relation to risk factors. This research was descriptive, prospective and cross-sectional and was carried out 61 students from the aforementioned institution, who participated voluntarily and met the inclusion criteria. To conclude the study, 41% corresponding to 25 students were found to have tested positive for H. pylori, in additionto this, and based up on the tabulation and analysis of the surye’s results, the diferent risk factors influential to contracting this bacteria were observed; these factors were: food dispensed by street vendors and soft drinks, with the rate of 88% of the infected patients; not washing the food before eating represented 72% and the consumption of water directly from the tap was 64% of the infected people; 80% do not wash their hands before eating; 40% do not wash their hands after leaving the bathroom, finally, the risk factor of alcohol and tabacco was 52% of the infected population. Considering everything aforementioned, it is important that students assess and avoid consuming food sold by street vendors, it is also important to educate people on the damage caused by this bacterium. Additionally, it is vital to track students who tested positive for H. pylori and carry out similar investigations in other educational institutions. Keywords: Helicobacter pylori, risk factors, immunochromatography method